Erosión - Underwood, Carlos; Santiago, Sergio (Saudade Producciones, 2016)
Independent documentary that addresses the different environmental problems in the north of Quintana Roo region, located in the Mexican Caribbean, caused by the rapid tourism development and uncontrolled population growth.--